Overcoming the limitations of PDB format (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
The Protein Data Bank is a repository for the 3-D structuraldata of large biological molecules, such as proteins andnucleic acid. The PDB is a key resource in the areas ofstructural biology, structural genomics. Most major scientificjournals, and some funding agencies, such as the NIH in theUSA, now require scientists to submit their structure data tothe PDB. If the contents of the PDB are thought of as primarydata, there are hundreds of derived databases that categorizethe data differently. For example, both SCOP and CATHcategorize structure according to type of structure andassumed evolutionary relations; GO categorize structuresbased on genes. In this paper, we will describe how toovercome the limitations of PDB format.